Efektivitas Model Pembelajaran Problem Based Learning (PBL) Terhadap Peningkatan Kemampuan Berpikir Kreatif Matematis Siswa SMK: Kemampuan Berpikir Kreatif, Problem Based Learning - Ningrum, Mira; Puadi, Evan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The main problem in this research is the low ability of students' mathematical creative thinking. the purpose of this study was to determine the effectiveness of the problem-based learning model for the mathematical creative thinking skills of vocational students. This research was carried out at SMK Negeri 5 Kuningan. The sample was taken by purposive sampling consisting of class X TKJ D (Experimental Class) and class X TKJ E (Control Class). The number of students in both classes is 70 students. The results of testing the hypothesis on the posttest data using the independent t-test showed that the hypothesis (????0) was rejected while the alternative hypothesis (????1) was accepted. This shows that there are differences in students' mathematical creative thinking abilities after applying the problem-based learning model to the experimental group and the conventional model to the control group. Improving students' mathematical creative thinking skills using the problem-based learning model based on the pre-test and post-test scores (N-Gain 0.4197 medium category). So, the conclusion of this study is that the use of problem-based learning models is effective in improving students' mathematical creative thinking skills, and almost half of students, namely 46.32%, respond well to problem-based learning models in learning mathematics.